2020
DOI: 10.1038/s41598-020-79508-3
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with 28-day all-cause mortality in older severe COVID-19 patients in Wuhan, China: a retrospective observational study

Abstract: We aimed to analyse clinical characteristics and identify risk factors predicting all-cause mortality in older patients with severe coronavirus disease 2019 (COVID-19). A total of 281 older patients with severe COVID-19 were categorized into two age groups (60–79 years and ≥ 80 years). Epidemiological, clinical, and laboratory data, and outcome were obtained. Patients aged ≥ 80 years had higher mortality (63.6%) than those aged 60–79 years (33.5%). Anorexia and comorbidities including hypertension, diabetes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 43 publications
4
25
0
Order By: Relevance
“…Six studies initially identified in preprint were subsequently excluded since they had not been peer-reviewed and published by 28 th January 2021; additionally, one study that was initially included based on preprint was subsequently removed since the peer-reviewed version did not meet our study's inclusion criteria. In total, 59 studies [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] were selected for the qualitative synthesis, of which 39[ [23] , [24] , [25] , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six studies initially identified in preprint were subsequently excluded since they had not been peer-reviewed and published by 28 th January 2021; additionally, one study that was initially included based on preprint was subsequently removed since the peer-reviewed version did not meet our study's inclusion criteria. In total, 59 studies [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] were selected for the qualitative synthesis, of which 39[ [23] , [24] , [25] , …”
Section: Resultsmentioning
confidence: 99%
“…This is perhaps not surprising given the urgency with which data were being collected, reported and updated at that time. Subsequent comparison of the authors, site of the study and the date of recruitment and follow-up identified 22 studies with potentially overlapping populations [ 27 , [34] , [35] , [36] , [37] , 39 , 43 , 49 , 54 , 55 , [58] , [59] , [60] , 68 , 69 , 71 , 72 , 74 , 78 ]. To avoid the double counting of patients we included only the largest (by participant numbers) of the potentially overlapping studies in the quantitative analysis.…”
Section: Resultsmentioning
confidence: 99%
“…A flowchart documenting the literature review process is shown in Figure S1 and a comprehensive list of variables that were found during this search is given in Table S1 . The variables were broadly categorized into the following groups: age 10 , 12 , 13 , 14 , 15 , 16 , 17 , 19 , 20 , 30 and comorbidities, 11 , 13 , 14 , 15 , 17 , 18 , 23 , 24 , 25 , 31 , 32 , 33 , 34 respiratory, 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 renal, 21 , 33 , 35 coagulation, 10 , 13 , 17 , 22 , 27 , 30 , 36 , 37 inflammatory,…”
Section: Methodsmentioning
confidence: 99%
“…In this regard, some demographic features and markers of illness severity have been reported as helpful in identifying patients at particularly high mortality risk. They have included older age, 10 , 12 , 13 , 14 , 15 , 16 , 17 , 19 , 20 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 male sex, 11 , 12 , 14 , 24 , 25 , 31 various comorbidities, 11 , 13 , 14 , 15 , 17 , 18 , 25 , 31 , 32 , 34 acute kidney injury, 21 , 33 , 35 coagulation problems, 10 , 13 , 17 , 22 , 27 , 30 , 36 , 37 increased markers of inflammation, 12 , 13 , 15 , 26 , 28 , 29 , 30 , 34 abnormal blood cell counts…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation